1997
DOI: 10.1295/polymj.29.574
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Polyimides Based on 2,3,5-Tricarboxycyclopentyl Acetic Dianhydride

Abstract: ABSTRACT:Soluble polyimides with polyalicyclic structure were prepared by reactions of 2,3,5-tricarboxycyclopentyl acetic dianhydride (TCA-AH) with aromatic diamines. The two-step polymerization systems including poly(amic acids) synthesis and solution imidization using pyridine and acetic anhydride were performed and soluble polyimides with high inherent viscosities and high imidization ratios were obtained. TCA-AH polyimides exhibited high thermal stability in air and nitrogen, and good solubility in common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…The dianhydride moieties of HP-and CP-PIs are more flexible or asymmetric than that of CB-PI, which lowers their T g s. Among them, the T g of TC-PI was the lowest (280 °C). Although it was reported that thermal degradation of a fully imidized semialiphatic PI prepared from TCA and 4,4'-diaminodiphenyl ether (TCA/ODA) was not observed up to 400 °C [13], a weight loss was readily observed at around 240 °C for a TC-PI film cured at 230 °C. As described below, this weight loss is attributable to the imidization reaction of residual PAA component due to its low φ i .…”
Section: T G and In-plane Cte Of Pismentioning
confidence: 99%
See 1 more Smart Citation
“…The dianhydride moieties of HP-and CP-PIs are more flexible or asymmetric than that of CB-PI, which lowers their T g s. Among them, the T g of TC-PI was the lowest (280 °C). Although it was reported that thermal degradation of a fully imidized semialiphatic PI prepared from TCA and 4,4'-diaminodiphenyl ether (TCA/ODA) was not observed up to 400 °C [13], a weight loss was readily observed at around 240 °C for a TC-PI film cured at 230 °C. As described below, this weight loss is attributable to the imidization reaction of residual PAA component due to its low φ i .…”
Section: T G and In-plane Cte Of Pismentioning
confidence: 99%
“…imidization reaction, are complicated and not efficient due to their structural isomerism and large steric hindrance. Thereby, the φ i of such semialiphatic PIs are frequently difficult to increase at lower temperature [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[1] In general, polyimides (PI) are prepared by a two-step process; first, diamines react with dianhydrides in aprotic polar solvents at room temperature to give poly(amide acid)s (PAA), the precursor of polyimides; second, poly (amide acid)s are converted to polyimides by either thermal or chemical imidization. Recently, new polyimides with various functional groups which show high solvent solubility, [2][3][4] high photosensitivity, [5][6][7] and photoconductivity, [8][9][10] have been actively investigated. Although polyimides have been widely used in microelectronics and space industry, their apparent color from yellow to brown has limited their application in optical communication and liquid crystal display devices.…”
Section: Introductionmentioning
confidence: 99%
“…Polyimides derived from 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropanedianhydride (6FDA), [12][13][14] are well known to be very transparent. I n recent years, polyimide prepared from alicyclic diamine [1 5-1 7] or alicyclic dianhydride [2,18] have been attracting much interest because of their good transparency, solubility, photochen ical and dielectric properties as well as good thermal stability. In our previous paper, [18] ultraviolet/visible absorption spectra and fluorescence spectra were investigated for transparent polyimides, PI(CBDA/DPM), PI(CBDA/ 6FdA), and PI (CBDAJDCHM) based on alicyclic dianhydride, 1 ,2 :3 ,4-cyclobutanetetracarboxylic dianhydride (CBDA), with an aromatic diamine, 4,4'-diaminodiphenylmethane (DPM), a fluorinated diamine, 2,2-bis(4-diaminodiphenyl)hexafluoropropane (6FdA), and an alicyclic diamine, 4,4'-diaminodicyclohexylmethane (DCHM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation